The Effect of Drinks and Temperature on the Staining of Resin Composites Coated with Surface Sealants - Hui R (Journal of Dental Biomaterial, 2014)
Statement of problem: Surface staining of resin composite by dietary factors may be modified by the placement of a low-viscosity surface sealant aimed at reducing surface voids and defects occurring after light-curing and polishing. Objectives: The aim of this study was to investigate the staining effect of various drinks and temperatures on the surface sealant (Fortify Plus™) sealed on a nano-filled resin composite (Supreme XTE™) after artificial aging at different temperatures. Materials and Methods: Surface sealant was applied on one surface of forty resin composite discs (10×2 mm). Five discs each were immersed in test solutions of black cola, commercial dark grape juice, coffee and distilled water (negative control). Discs were either placed at 4°C (20 discs) or 37°C (20 discs) and the colour difference (ΔE) was calculated based on the colour coordinates at 0 (baseline), 7, 14 and 28 days of staining treatment. Two-factor with replication analysis was carried out with ANOVA. Results: The results showed significant discolouration after 28 days immersion in coffee (P<0.001) and grape juice group (P<0.001). Surface sealant significantly affected colour changes in coffee and grape juice group (P=0.002). Higher temperatures in coffee and grape juice also significantly increased the effect of staining (P<0.001). Conclusions: Surface sealant was able to reduce discolouration in the grape juice group only. A lower temperature of 4°C caused less staining in coffee and grape juice groups as compared to the 37°C corresponding test groups. Prolonged immersion time significantly increased discolouration in coffee and grape juice groups.